2012
DOI: 10.1109/tnsre.2012.2189163
|View full text |Cite
|
Sign up to set email alerts
|

A Nonlinear Model for Hippocampal Cognitive Prosthesis: Memory Facilitation by Hippocampal Ensemble Stimulation

Abstract: Collaborative investigations have characterized how multineuron hippocampal ensembles encode memory necessary for subsequent successful performance by rodents in a delayed nonmatch to sample (DNMS) task and utilized that information to provide the basis for a memory prosthesis to enhance performance. By employing a unique nonlinear dynamic multi-input/multi-output (MIMO) model, developed and adapted to hippocampal neural ensemble firing patterns derived from simultaneous recorded CA1 and CA3 activity, it was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 78 publications
(122 reference statements)
5
75
1
Order By: Relevance
“…Given also its pivotal roles in memory functions, it has been one of the most studied regions in the brain, and the first target of neural engineers in building cortical prostheses that can restore cognitive functions (Berger et al 2005(Berger et al , 2011Hampson et al 2012Hampson et al , 2013. In this chapter, we will describe the hippocampal microcircuit with an emphasis on its functional consequences in the context of building hippocampal memory prostheses for restoring memory functions.…”
Section: Introductionmentioning
confidence: 99%
“…Given also its pivotal roles in memory functions, it has been one of the most studied regions in the brain, and the first target of neural engineers in building cortical prostheses that can restore cognitive functions (Berger et al 2005(Berger et al , 2011Hampson et al 2012Hampson et al , 2013. In this chapter, we will describe the hippocampal microcircuit with an emphasis on its functional consequences in the context of building hippocampal memory prostheses for restoring memory functions.…”
Section: Introductionmentioning
confidence: 99%
“…Our test data are acquired from the male Long-Evans rats aged from four to six months which are trained to perform the delayed nonmatch-to-sample (DNMS) task [11]. The hippocampal neuronal firing activities are recorded by the multielectrode array when the rats are performing the task.…”
Section: Resultsmentioning
confidence: 99%
“…Factors such as LTP promote the chance that groups of neurons with multiple synaptic connections will tend to fire in coordinated spatiotemporal patterns that underlie information processing for specific sensory events when frequently repeated. In previous investigations a nonlinear multi-input multi-output (MIMO) math model was employed to analyze cell firing across large neuron populations in the same structures (Berger et al 2011; Hampson et al, 2012b; Hampson et al, 2012c). In those studies it was demonstrated that the derived spatiotemporal firing patterns across all cells in the population were hierarchical, and provided important information-specific ‘firing codes’ during performance of complex memory tasks.…”
Section: Neurons and Networkmentioning
confidence: 99%